Efektivitas Atraktan Air Limbah Cucian Pakaian pada Ovitrap Nyamuk Aedes sp. di Kelurahan Sukajaya Kecamatan Sukarami - Alfath, Mochammad Nanda Ardani; Ramayanti, Indri; Prameswarie, Thia; Anggina, Dientyah Nur (Faculty of Medicine, 2025)
Dengue Hemorrhagic Fever (DHF) is more common during the rainy season in Indonesia, and it is caused by dengue virus infection by the bite of Aedes sp. mosquitos. DHF vector control can be achieved through a variety of approaches, one of which is the physical method of employing ovitraps with the addition of readily available laundry wastewater attractants that contain mosquito-attracting chemicals. The purpose of this study to assess the efficacy of laundry wastewater attractants in ovitraps Aedes sp.. The research design adopted was quasi-experimental. Sampling was done by purposive sampling and based on Federer's formula, 6 houses in RT 46 Sukajaya Village, Sukarami Subdistrict were obtained as samples according to inclusion criteria, namely houses with large yards and many trees. This study used laundry wastewater as an attractant in ovitraps placed inside and outside residents' homes with concentrations of 10%, 30%, and 60% for three repetitions. Research data is analyzed using ANOVA and Chi-square tests. The study found that, the ovitrap with a 60% concentration of laundry wastewater attractant placed inside and outside the house produced the most Aedes sp. eggs.